2017
DOI: 10.18343/jipi.22.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Marker Compound of Jati Belanda (Guazuma ulmifolia Lamk) Extract as Anti-Cholesterol

Abstract: ABSTRAK Daun jati belanda (Guazuma ulmifoliaLamk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Di Lombok Timur dibeberapa wilayah, jarak kepyar tumbuh liar dan menjadi tanaman yang dianggap sebagai gulma yang mengganggu, sehingga masyarakat menebang dan membuangnya, padahal ternyata tanaman tersebut memiliki banyak manfaat dalam pengobatan (Al-Mamun et al, 2016). Tumbuhan ini mengandung flavonoid kuhusnya kuersetin, glikosida, saponin, tanin, alkaloid, kaempferol dan steroid yang dipercaya memiliki banyak manfaat dalam pengobatan salah satunya penyakit kardiovaskular (Nishizawa, 2020); (Widyaningrum, 2015); (Batubara et al, 2017).…”
Section: Pendahuluanunclassified
“…Di Lombok Timur dibeberapa wilayah, jarak kepyar tumbuh liar dan menjadi tanaman yang dianggap sebagai gulma yang mengganggu, sehingga masyarakat menebang dan membuangnya, padahal ternyata tanaman tersebut memiliki banyak manfaat dalam pengobatan (Al-Mamun et al, 2016). Tumbuhan ini mengandung flavonoid kuhusnya kuersetin, glikosida, saponin, tanin, alkaloid, kaempferol dan steroid yang dipercaya memiliki banyak manfaat dalam pengobatan salah satunya penyakit kardiovaskular (Nishizawa, 2020); (Widyaningrum, 2015); (Batubara et al, 2017).…”
Section: Pendahuluanunclassified
“…In guazuma leaves, the potential compounds associated with antioxidant and anti-triglyceride activity included flavonoid, tannins, carotenoid and phenolic acids [19]. Batubara [20] successfully fractionated quercetin in guazuma leaf extracts which could reduce cholesterol level.…”
Section: Antioxidant Activity Of Guazuma Leavesmentioning
confidence: 99%
“…Research conducted by (Ulfah & Iskandar, 2020), revealed that the aqueous extract of Dutch teak leaves at a dose of 50 mg/Kg BW was able to significantly inhibit the increase in total and LDL cholesterol levels in the control group. Quercetin in Dutch teak leaf extract owns a fairly high level and is efficacious in lowering cholesterol levels (Batubara et al, 2017). Supriani's research et al (2019), uncovered a change in cholesterol levels after administering Dutch teak leaf tea in Kedungsari Hamlet, Balongsari Megaluh Village.…”
Section: Introductionmentioning
confidence: 99%